2017
DOI: 10.1038/srep40267
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-dependent electronic structure and film formation of MAPbI3 perovskites

Abstract: We present investigations on the interface formation between the hybrid perovskite MAPbI3 and various substrates, covering a wide range of work functions. The perovskite films are incrementally evaporated in situ while the electronic structure is evaluated using photoelectron spectroscopy. Our results show that there is an induction period in the growth of the perovskite during which volatile compounds are formed, catalyzed by the substrate. The duration of the induction period depends strongly on the nature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
341
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(362 citation statements)
references
References 56 publications
(74 reference statements)
20
341
0
1
Order By: Relevance
“…[54] At this point it is worth summarizing the effects of the IL on the substrate and on the perovskite. [46,47,56] This is effectively what we see here in the WF shift of the perovskite, where as the WF of the substrate decreases, there is a corresponding decrease in the WF of the perovskite crystallized atop the substrate. This has previously been observed for various types of materials such as polymers, where the deposition of the polymer on a variety of different substrates causes a shift in the work func tion of the substrate.…”
Section: Resultssupporting
confidence: 62%
“…[54] At this point it is worth summarizing the effects of the IL on the substrate and on the perovskite. [46,47,56] This is effectively what we see here in the WF shift of the perovskite, where as the WF of the substrate decreases, there is a corresponding decrease in the WF of the perovskite crystallized atop the substrate. This has previously been observed for various types of materials such as polymers, where the deposition of the polymer on a variety of different substrates causes a shift in the work func tion of the substrate.…”
Section: Resultssupporting
confidence: 62%
“…1b) than the diffusion in bulk MAPbI 3 crystal, possibly driven by the local electronic field in the vicinity of the interface. A previous photoemission study [27] reported that the stoichiometry of MAPbI 3 within a few nm of the interfaces can be affected by the substrates, and the interface can have a band bending as a result of the dipole formation, in contrast to the commonly assumed flat band condition. A comparative study on the device performance [4] also proposed the possibility of ionic accumulation at the interface causing a steep band bending at the interface and a flat band in the rest of perovskite in order to explain the insensitivity of V oc to the VBM of the HTMs.…”
mentioning
confidence: 97%
“…In particular, MAI seems to have a varying affinity to physisorb on certain substrates and might even decompose, which hinders the formation of the perovskite phase in the first few nanometers. [74,75] Nevertheless, this issue can be overcome by employing a fullerene intermediate layer, allowing the fabrication of perovskite solar cells with a high stabilized efficiency. [76] For more details on vapor-based techniques, we refer the reader to the recently published review by Ono et al [77] Another emerging research topic concerns lower-dimensional perovskites that form by substitution of the organic compound with bulkier molecules, generally employing longer alkylammonium chains.…”
Section: Alternatives To Solution-processed Thin Filmsmentioning
confidence: 99%